2021
DOI: 10.1123/ijspp.2020-0362
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Versus Criterion Heart Rate Variability Among International-Level Girls’ Field Hockey Players

Abstract: Purpose: To assess heart rate (HR) variability responses to various markers of training load, quantify associations between HR variability and fitness, and compare responses and associations between 1-minute ultrashort and 5-minute criterion measures among a girls’ field hockey team. Methods: A total of 11 players (16.8 [1.1] y) recorded the logarithm of the root mean square of successive differences (LnRMSSD) daily throughout a 4-week training camp. The weekly mean (LnRMSSDM) and coefficient of variation (LnR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…These results can be observed in detail in Table 1 . These findings are in line with previously published articles that showed a reduction of LnRMSSD and increases in LnRMSSDcv during overload periods in collegiate female soccer players [ 27 ] and international female hockey players [ 37 ]. Thus, it seems that these vagal markers could be used to track the response to the training of professional female cyclists both at sea level and in moderate altitude conditions using a smartphone application.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results can be observed in detail in Table 1 . These findings are in line with previously published articles that showed a reduction of LnRMSSD and increases in LnRMSSDcv during overload periods in collegiate female soccer players [ 27 ] and international female hockey players [ 37 ]. Thus, it seems that these vagal markers could be used to track the response to the training of professional female cyclists both at sea level and in moderate altitude conditions using a smartphone application.…”
Section: Discussionsupporting
confidence: 93%
“…LnRMSSDcv showed a mean change of −30% during the first week of the TC and the individual change ranged between 6% and −69%. Thus, it seems that the exposition to moderate levels of hypoxia did not produce enough stress to induce reductions in the vagal activity in this population and this reduction could be due to the concomitant reduction in the TL, as seen before in other sports [ 37 , 39 , 40 ]. It is important to note that these markers evolved differently among individuals.…”
Section: Discussionmentioning
confidence: 57%
“…Second, all included studies used single-time point HRV values, while previous studies suggest that average HRV values from a series of consecutive days should be used to account for and to quantify day-to-day HRV lability [ 30 , 110 ]. Indeed, improvements in aerobic fitness are often associated with increased stability in daily RMSSD values [ 111 , 112 , 113 ], quantified by the coefficient of variation, and more stable RHR profiles are associated with a reduced risk of cardiovascular events [ 114 ]. Third, measurements were carried out in the supine position and the seated position in studies that performed lab-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations and one case study reported greater reductions in vagal-mediated HRV relative to baseline throughout predefined training versus better maintenance of values with HRV-guided training [ 17 , 18 , 65 ]. Moreover, observational studies frequently report greater aerobic fitness improvements among individuals who exhibit higher and more stable vagal HRV values throughout predefined training [ 37 , 66 , 67 , 68 , 69 , 70 , 71 ]. Contrastingly, greater day-to-day fluctuations in HRV are often observed in fatigued athletes and can occur with [ 58 , 68 , 72 ] or without [ 66 , 73 ] purposeful overload.…”
Section: Discussionmentioning
confidence: 99%